Qualitative Content Analysis Related to the Use of Instagram @pertamina as a Communication Technology in Response to Post Fire Crisis Plumpang Depo March 2023 - Cornelius, Maria Adeline; Kurniawati, Meilinda; Putri, Tania Rizqia (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2024)
On March 3, 2023, a fire occurred at the Pertamina Plumpang Depot, Koja, North Jakarta. Transparency and good communication regarding the responsibilities carried out by Pertamina are important steps in maintaining trust and minimizing the negative impact on the company's reputation. Situational Crisis Communication Theory can be applied in managing communication in crisis situations. The @pertamina Instagram account shows empathy and concern in dealing with the crisis caused by this fire. This article aims to analyze the use of Instagram as a crisis response strategy after the Plumpang Depo fire on March 3, 2023, with a focus on content on the @pertamina account. A qualitative content analysis method was used in this study, with the unit of analysis in the form of content on Instagram @pertamina in the post-fire period at the Plumpang Depo, namely between 4 and 8 March 2023. Data collection was carried out through observing content, including uploads, descriptions on images, and information on the post, and there are ten contents examined. In this study, it was found that Pertamina uses a crisis response strategy model in the form ofdeal response strategy in responding to the crisis. The @pertamina Instagram account is used as a communication technology that becomes a bridge to the public in dealing with crises with consistency and in accordance with society's expectations, such as providing compensation, apologizing, and showing regret, without trying to prove the truth or allude that the crisis originates from factors outside the organization's